2018
DOI: 10.1002/chem.201802973
|View full text |Cite
|
Sign up to set email alerts
|

From Indium‐Doped Ag2S to AgInS2 Nanocrystals: Low‐Temperature In Situ Conversion of Colloidal Ag2S Nanoparticles and Their NIR Fluorescence

Abstract: Focusing on ternary I-III-VI colloidal nanocrystals (NCs) synthesized with precise control of the composition (from doping to ternary composition) and NIR fluorescence performance, monodisperse binary In -doped Ag S NCs and ternary AgInS NCs have been achieved successfully by facile low-temperature in situ conversion of colloidal Ag S nanoparticles. In ions were inserted into the crystal lattice of Ag S NCs at a relatively low temperature as dopant and ternary AgInS NCs were obtained at a higher temperature fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 40 publications
(69 reference statements)
0
8
0
Order By: Relevance
“…In both cases, when the DMTU solution was injected, a pale-yellow solution (Ag-dodecanethiol complex) became orange, red, and finally dark brown, which indicated the formation of the Ag 2 S intermediate. The Ag 2 S intermediate was subsequently converted to AgInS 2 by cation exchange or resource-host-type reactions [29,30]. Figure 1 shows the UV-Vis, PL spectra, and TEM images and size distribution histograms of AgInS 2 QDs synthesized by the immediate injection and dropwise injection methods.…”
Section: Synthesis Of High-quality Agins 2 Quantum Dotsmentioning
confidence: 99%
“…In both cases, when the DMTU solution was injected, a pale-yellow solution (Ag-dodecanethiol complex) became orange, red, and finally dark brown, which indicated the formation of the Ag 2 S intermediate. The Ag 2 S intermediate was subsequently converted to AgInS 2 by cation exchange or resource-host-type reactions [29,30]. Figure 1 shows the UV-Vis, PL spectra, and TEM images and size distribution histograms of AgInS 2 QDs synthesized by the immediate injection and dropwise injection methods.…”
Section: Synthesis Of High-quality Agins 2 Quantum Dotsmentioning
confidence: 99%
“…36 Figure S12B demonstrated that In 3d 5/2 and 3d 3/2 peaks were located at 444.7 and 452.3 eV, which was in agreement with +3 state of In. 37 The theoretical simulation (Figure S13 and Table S4) revealed the coordination environments of Cu and In in OA-CdS SNCs. Due to the lowest formation energy (E f = À1.013 eV) of substitution, Cu-and In-doped OA-CdS SNCs, Cu and In dopants preferred to coordinate with S atoms and occupy the Cd sites.…”
Section: Tunable Pl Property Of Cu In Dual-doped Cds Sncs Triggered By Sveice Strategymentioning
confidence: 95%
“…Series of such NCs in group I‐III‐VI and I‐II‐IV‐VI semiconductors are extensively studied and explored for designing both light‐emitting and harvesting devices . Among different synthesis methods of these multinary NCs, in situ chemical conversion is one efficient protocol for keeping the intrinsic morphologies of starting materials . For instance, Pradhan and his co‐workers obtained core/shell Sb 2 Se 3 /Cu 3 SbSe 3 nanorod heterostructures with NIR‐localized surface plasmon resonance (SPR) .…”
Section: Figurementioning
confidence: 99%
“…[7][8][9][10] Among different synthesis methods of these multinary NCs, in situ chemical conversion is one efficient protocol for keeping the intrinsic morphologies of starting materials. [11] For instance, Pradhana nd hisc o-workers obtained core/shell Sb 2 Se 3 /Cu 3 SbSe 3 nanorod heterostructures with NIR-localized surface plasmon resonance (SPR) . It wasa chieved by adding Cu I under specific reaction conditions to presynthesized Sb 2 Se 3 rods.…”
mentioning
confidence: 99%